The health literacy of university students in North Cyprus - Sariyar, Sultan; Kilic, Hulya Firat (Oxford Univ Press, 2021)
Health literacy is individuals' motivation and ability to obtain, understand, evaluate and use health information. Health literacy is very important during university education when students have the ability to acquire and accumulate knowledge of the best way. The aim of this study was to determine the health literacy of university students. The sample of this descriptive cross-sectional study was composed of 365 students who were first-time visitors at the health center of a private university in Northern Cyprus between May and July 2017. An introductory information form and the Adult Health Literacy Scale (AHLS) were used as data collection tools. The mean AHLS score of the students was found as 13.91 +/- 2.90. Health literacy was found to be lower for male students and students with more years of study. The students with low daily alcohol use had higher AHLS scores. The results of the study suggest that curricula should be revised to raise the health literacy of university students to the highest level. It is important to organize conferences, seminars and scientific activities to improving the health literacy of male students and students with more years of study. Due to the limitations of studies of health literacy in North Cyprus, future studies should be conducted with larger samples and different measurement tools.
Keywords: health literacy; Cyprus; university students